THE IMPACT OF ENGLISH AS A GLOBAL LANGUAGE ON LINGUISTIC DIVERSITY - Arabboyeva Sarvinoz Jasurbek kizi (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
This article analyzes the role of English as a global language and its importance in various fields. The role of the English language in international spheres, namely communication, education, science, business, technology, and culture, is covered in detail.